Enigma - Harris, Robert (London : Arrow Books, 1996)
A member of a top-secret team of British cryptographers, Tom Jericho succeeds in cracking "Shark," the impenetrable operational cipher used by Nazi U-boats, but when the Germans change the code, Jericho must break the new code before the traitor among his group can stop him.
Keywords: World War, 1939-1945 -- Secret service -- Fiction; Thrillers (Fiction)